Causes and consequences of adult sex ratio imbalance in a historical U.S. population. (19th September 2017) - Schacht, Ryan; Smith, Ken R.
Abstract : The responsiveness of individuals to partner availability has been well-documented across the literature. However, there is disagreement regarding the direction of the consequences of sex ratio imbalance. Specifically, does an excess of males or females promote male–male mating competition? In an attempt to clarify the role of the adult sex ratio (ASR) on behaviour, here we evaluate both competing and complimentary expectations derived from theory across the social and biological sciences. We use data drawn from a historical, nineteenth century population in North America and target several life-history traits thought to be affected by partner availability: age at first birth, relationship status, completed fertility and longevity. Furthermore, we assess the role of various contributors to a population's ASR. We find that both the contributors to and consequences of sex ratio imbalance vary over time. Our results largely support predictions of greater male pairbond commitment and lesser male mating effort, as well as elevated bargaining power of women in response to female scarcity. After reviewing our findings, and others from across the literature, we highlight the need to adjust predictions in response to ASR imbalance by the: (i) culturally mediated mating arena, (ii) variable role of demographic inputs across time and place, (iii) constraints to behavioural outcomes across populations, and (iv) ability and accuracy of individuals to assess partner availability. This article is part of the themed issue 'Adult sex ratios and reproductive strategies: a critical re-examination of sex differences in human and animal societies'.